SWOT ANALYSIS OF KUE SAPIK GULA AREN AS A SUPPORTING TOURISM ATTRACTION OF SOLOK SELATAN DISTRICT - Aocta Riva Auberni; Pepy Afrilian; Mandalia, Siska (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2023)
This study aims to analyze the strengths, weaknesses, opportunities, and threats of the Kue Sapik Gula Aren as a support for the tourist attraction of South Solok Regency. The research method used is through a qualitative approach using the SWOT analysis method and the data used in this study are primary and secondary data, data collection techniques by observation and interviews. The data obtained from the results of data collection is then analyzed using SWOT analysis to find out what are the strengths, weaknesses, opportunities, and threats of the Kue Sapik Gula Aren as asupporting tourist attraction in South Solok Regency. Based on the results of the study, it shows that the Kue Sapik Gula Aren has the strengths 1 it has a unique taste that comes from palm sugar 2 Kue Sapik Gula Aren can only be found in South Solok 3 has been certified halal from the MUI, and the opportunity 1 can be a support for new tourist attractions in South Solok Regency 2 promote traditional culinary 3 promote the economy of the surrounding community. With these strengths and opportunities, can take advantage of existing opportunities while minimizing weaknesses and also being able to overcome various kinds of threats from the Kue Sapik Gula Aren. Thus, this Kue Sapik Gula Aren can be used as a support for the tourist attraction of South Solok Regency.